2010
DOI: 10.1021/ac100229k
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Thin-Film Reactor for Photochemical Vapor Generation

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Versatile thin-film reactor for photochemical vapor generation Zheng, Chengbin; Sturgeon, Ralph E.; Brophy, Christine; Hou, Xiandeng http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT AVANT D'UTILISER CE SITE WEB. NRC Publications Record / Notic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…24 Among them, acetic acid was found to be more efficient for the PVG of Sb. 32,33 During the preliminary experiments, efficient photochemical reduction of Sb occurs (steady-state signal obtained) if the concentration of acetic acid is in a range of 10−30% (v/v), as shown in Figure 2a. Only background signal was obtained when the PVG UV lamp was switched off, confirming sensitivity enhancement of Sb was indeed due to PVG.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 Among them, acetic acid was found to be more efficient for the PVG of Sb. 32,33 During the preliminary experiments, efficient photochemical reduction of Sb occurs (steady-state signal obtained) if the concentration of acetic acid is in a range of 10−30% (v/v), as shown in Figure 2a. Only background signal was obtained when the PVG UV lamp was switched off, confirming sensitivity enhancement of Sb was indeed due to PVG.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our previous work [13] showed that the photochemical vapor generation efficiency of mercury is not only dependent on the concentration of LWM organic compounds but also determined by the UV irradiation time. Meanwhile, the optimal irradiation time for different elements varies: I, Co, and Hg can be easily reduced to their volatile species and then 5 s of UV irradiation time is more than enough.…”
Section: Determination Of Mercury In Water By Photo-cvg-afsmentioning
confidence: 99%
“…Therefore, it is desired to develop a new CVG method to replace the conventional techniques. Recently, photochemical cold vapor generation (Photo-CVG) has been developed to eliminate the use of unstable or toxic reductants such as SnCl 2 and NaBH 4 [13][14][15][16][17]. Despite increasing interest in Photo-CVG over the past several years, this technique has been used for the determination of mercury but not for mercury removal.…”
Section: Introductionmentioning
confidence: 99%
“…This modified system has been successfully applied to the determination of iodine in sediments and biological materials. Recently, a versatile thin-film reactor in order to achieve better performance of PVG was developed by the same group [55]. The device utilized a vertical central quartz rod which was inside a concentric quartz tube served both as a generator and a gas liquid separator.…”
Section: Photochemical Vapor Generation Systemsmentioning
confidence: 99%